Clientelism in Bandar Lampung’s Mayor Election 2015: A case study of Herman H. N. and M. Yusuf Kohar as candidate pair - Robi Cahyadi Kurniawan; Dedy Hermawan; Himawan Indrajat (Masyarakat, Kebudayaan dan Politik, 2018)
Clientelism is a renewal of the patronage concept, usually referred to as patron-client in some scientific literature. Research about patron-client in the context of domestic politics, specifically in regional elections, is rarely conducted. Previous studies have mostly examined national-level elections, namely president and legislative. Therefore, this research has tried to answer the question on how the clientelism process worked during the Mayor’s Election in Bandar Lampung in 2015, particularly for candidate pair of Herman HN and M. Yusuf Kohar. This research was conducted in Bandar Lampung city from September 2016 to January 2017 as a part of the authors’ dissertation. It employs qualitative method using in-depth interview method on respondents who are related to research objects. The informants consisted of political practitioners, members of campaign teams, and academicians. The findings showed that clientelism among voters occurred during mayor election in Bandar Lampung 2015. There is a mutualism symbiosis between the incumbent candidate (Herman HN) and the voters in Mayor Election of Bandar Lampung in 2015. The voters’ votes can be influenced using the imagery portrayed by the candidates, particularly Herman HN. They can also be influenced by distributive politics or by giving what the voters’ needs through infrastructure politics (such as the construction of roads and bridges), free education, free health care, and social/religion aids. The candidate pair who won the election had different campaign teams.